2020
DOI: 10.1101/2020.04.19.20071373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalable and Resilient SARS-CoV-2 testing in an Academic Centre

Abstract: The emergence of the novel coronavirus SARS-CoV-2 has led to a pandemic infecting more than two million people worldwide in less than four months, posing a major threat to healthcare systems. This is compounded by the shortage of available tests causing numerous healthcare workers to unnecessarily self-isolate. We provide a roadmap instructing how a research institute can be repurposed in the midst of this crisis, in collaboration with partner hospitals and an established diagnostic laboratory, harnessing exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…To address the dire need for increased testing, researchers across disciplines have quickly compared widely available commercial products, proposed repurposing existing reagents and infrastructure, and created novel laboratory solutions to optimize the COVID-19 testing pipeline. Academic researchers at a few institutions around the world have published detailed blueprints for establishing local pop-up testing centers, and others are likely to follow (Consortium and Doudna 2020;Sridhar et al 2020;Aitken et al 2020). A combination of testing approaches may be the most efficient way to fill the current gaps in testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the dire need for increased testing, researchers across disciplines have quickly compared widely available commercial products, proposed repurposing existing reagents and infrastructure, and created novel laboratory solutions to optimize the COVID-19 testing pipeline. Academic researchers at a few institutions around the world have published detailed blueprints for establishing local pop-up testing centers, and others are likely to follow (Consortium and Doudna 2020;Sridhar et al 2020;Aitken et al 2020). A combination of testing approaches may be the most efficient way to fill the current gaps in testing.…”
Section: Discussionmentioning
confidence: 99%
“…Many protocols use commercial reagents for lysis, including DNA/RNA Shield (Zymo Research), Buffer RLT (Qiagen), and MagNA Pure External Lysis Buffer (Roche). However, multiple researchers have recently found that when compared to commercial solutions, homemade solutions containing 4M (Scallan et al 2020;Sridhar et al 2020) or 5M (Aitken et al 2020) guanidinium thiocyanate work equally well to lyse samples and recover viral RNA after purification. However, these solutions contain strong denaturants and are therefore not compatible with addition directly into amplification reactions.…”
Section: Sample Lysis and Direct Additionmentioning
confidence: 99%
“…All the samples processing through the CCC pipeline was done in accordance with SOPs described recently 5 . A redefined reaction, running, and reporting SOP can be found in the Supplemental Methods.…”
Section: Methodsmentioning
confidence: 99%
“…An initial characterization of the technique was performed using 24 RNA samples purified from patient nasopharyngeal swabs, 12 of which were positive for SARS-CoV-2 as assessed by the CCC pipeline via RT-qPCR 5 . RT-LAMP could detect SARS-CoV-2 in the 12 positive samples with no amplification detected in all 12 negative samples, displaying 100% concordance to our current clinical diagnostic platform ( Figures 1C and 1E).…”
Section: Rt-lamp Test Validitymentioning
confidence: 99%
“…The RNA extraction process employs the open-source Bio-On-Magnetic-Bead (BOMB) protocol, which uses DIY reagents and is amenable to automation 21,22 . The use of open-source hardware and reagents allow labs to navigate around limited supply chains 23 . The OT-2 liquid handling robot has a low initial cost relative to other liquid handling robots, can utilise generic plasticware and run protocols written in the coding language Python 24,25 .…”
Section: Introductionmentioning
confidence: 99%